Correction: Grouping of chemicals for safety assessment: the importance of toxicokinetic properties of salicylate esters - Abdulkarim Najjar; Sébastien Grégoire; Beate Nicol; Andreas Natsch; Nazanin Golbamaki; Fanny Boisleve; Amaia Irizar; Brian Wall; Angus Swinscoe; Valérie Masini-Etévé; Kaushal Joshi; Anne Marie Api; et al. (Archives of Toxicology, 2025)

Grouping of chemicals for safety assessment: the importance of toxicokinetic properties of salicylate esters - Abdulkarim Najjar; Sébastien Grégoire; Beate Nicol; Andreas Natsch; Nazanin Golbamaki; Fanny Boisleve; Amaia Irizar; Brian Wall; Angus Swinscoe; Valérie Masini-Etévé; Kaushal Joshi; Anne Marie Api; et al. (Archives of Toxicology, 2025)
Grouping of chemicals has been proposed as a strategy to speed up the screening and identification of potential substances of concern among the broad chemical universe under REACH. Such grouping is usually based on shared structural features and should only be used for the prioritization objectives. However, additional considerations (as well as structural similarity) are needed, e.g., mode of action, metabolic pathways, chemical reaction products and physicochemical properties, when regulatory management measures are considered (such as restriction, harmonized classification and labeling). Guidance documents from the European Chemicals Agency (ECHA) recommend considering toxicokinetic information to enhance the robustness of the grouping; however, examples of this approach are lacking. Therefore, this paper shares findings on chemical grouping based on ADME data generated for multiple esters of salicylic acid. These differ with respect to chain length and branching of the alcohol moiety of salicylic acid ester, resulting in a wide range of lipophilicity (LogP 0.21–10.88). Since LogP impacts skin absorption, as well as hydrolysis by carboxylesterases, the bioavailability and thus internal exposure to topically applied salicylate esters can vary considerably. Therefore, we collected skin absorption and metabolism data for 41 salicylates using in vitro testing and in silico models and combined the information to group them according to their potential systemic exposure to the major metabolite, salicylic acid. The results show that, despite a similar general chemical structure, their toxicokinetics vary considerably, indicating the need for better understanding of ADME properties to assess the internal exposure for sound risk assessment.

In vitro to in vivo extrapolation to derive a metabolism factor for estimating the aggregate exposure to salicylic acid after dermal exposure of its esters - Abdulkarim Najjar; Sebastien Grégoire; Beate Nicol; Andreas Natsch; Nazanin Golbamaki; Fanny Boisleve; Amaia Irizar; Brian Wall; Angus Swinscoe; Valérie Masini-Etévé; Dan Selechnik; Anne Marie Api; et al. (Archives of Toxicology, 2024)
As part of the safety assessment of salicylate esters in cosmetics, we developed a metabolism factor based on in vitro to in vivo extrapolation (IVIVE) to provide a better estimation of the aggregate internal exposure to the common metabolite, salicylic acid. Optimal incubation conditions using human liver S9 were identified before measuring salicylic acid formation from 31 substances. Four control substances, not defined as salicylic esters but which could be mistaken as such due to their nomenclature, did not form salicylic acid. For the remaining substances, higher in vitro intrinsic clearance (CL int, in vitro ) values generally correlated with lower LogP values. A “High-Throughput Pharmacokinetic” (HTPK) model was used to extrapolate CL int, in vitro values to human in vivo clearance and half-lives. The latter were used to calculate the percentage of substance metabolised to salicylic acid in 24 h in vivo following human exposure to the ester, i.e. the “metabolism factor”. The IVIVE model correctly reproduced the observed elimination rate of 3 substances using in silico or in vitro input parameters. For other substances, in silico only-based predictions generally resulted in lower metabolism factors than when in vitro values for plasma binding and liver S9 CL int, in vitro were used. Therefore, in vitro data input provides the more conservative metabolism factors compared to those derived using on in silico input. In conclusion, these results indicate that not all substances contribute equally (or at all) to the systemic exposure to salicylic acid. Therefore, we propose a realistic metabolism correction factor by which the potential contribution of salicylate esters to the aggregate consumer exposure to salicylic acid from cosmetic use can be estimated.